The experience of using computer software for enhancing studying-training process in tertiary physical education. - Klopov R.V (Kharkov National Pedagogical University, 2010)
The article focuses on the present day situation with computer software which helps enhance the process of studying and training in tertiary physical education. It analyses and classifies the existing computer software according to its use in studying and training: modeling of technics of impellent actions; training and measuring systems; the pedagogical control over training process and development of impellent qualities; the analysis of competitive activity.